2013 IEEE 13th International Conference on Advanced Learning Technologies 2013
DOI: 10.1109/icalt.2013.99
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Performance in an Introductory Programming Course by Logging and Analyzing Student Programming Behavior

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(147 citation statements)
references
References 19 publications
2
137
1
7
Order By: Relevance
“…However studies to date are limited by a lack of verification, and a tendency to yield inconsistent results [23]. Additionally the previously researched predictors require the use of lengthy tests to gather predictive data.…”
Section: Introductionmentioning
confidence: 99%
“…However studies to date are limited by a lack of verification, and a tendency to yield inconsistent results [23]. Additionally the previously researched predictors require the use of lengthy tests to gather predictive data.…”
Section: Introductionmentioning
confidence: 99%
“…Watson et al [20] also found a significant correlation between the EQ and the scores of students in their data (r = 0.44). They proposed an extended algorithm called Watwin which takes into account the time a student spends in overcoming a particular error.…”
Section: Related Workmentioning
confidence: 89%
“…O autor verificou que o EQ possui uma correlação com a nota do aluno. Nesse mesmo caminho, [Watson et al 2013] criou uma derivação da métrica EQ, levando em consideração o tempo que o aluno levava para consertar o erro. O algoritmo proposto por Watson, chamado Watwin Score, obteve uma acurácia média de 68,8% ao longo do curso e atingiu 75,6% no final do curso, enquanto no trabalho de Jadud os resultados foram de 55,8% de acurácia média e de 60,0% ao final do curso, ambos para predição de desempenho [Watson et al 2013].…”
Section: Trabalhos Relacionadosunclassified